Geochemical Analogy Viscosity of Mid-Ocean Ridge Basalt as an Indicator for Determining the Location of Seafloor Hydrothermal Fields? - Li, Chuanshun; Wang, Guohuai; Yan, Shijuan; Du, Dewen (Frontiers in Earth Science, 2022)
Many achievements have been made in the exploration of seafloor polymetallic hydrothermal vents, however, it needs to further study how to discovery more potential new hydrothermal or massive sulfide fields. In this study, we collected 9818 major-element geochemical data sets of basalt samples from the Mid-Atlantic Ridge (MAR, 78°N–53°S) and the seafloor topographic data for eleven known hydrothermal vents (e.g., TAG, Snake Pit, MAR 22°30′N, Lilliput). Based on the different spatial distances between basalts and hydrothermal vents, we classified all the basalts into three categories: (1) basalt near known vent (focal objects of the research, 29 samples), (2) basalt around known vent (observed objects, 155 samples), and (3) other basalt of the MAR (as background basalt). Meanwhile, we used major element components of basalts to calculate the analogy viscosity and analyzed the possible correlation between analogy viscosity and the spatial distribution of seafloor hydrothermal vents. We found that the analogy viscosity of basalt near known vent fall into a narrow medium value range (~ 46.8 – ~ 68.5 Pa•s) contrasted with the range of background basalt values range (~ 4.0 – ~ 356.0 Pa•s). It infers that these basalts on the Mid-Atlantic Ridge with the medium values of analogy viscosity favor the formation of hydrothermal vents. However, due to the complexities of magmatic activity and fault structure, as well as the multi-stage water-rock reaction, whether the analogy viscosity of basalts can be used as an indicator for determining the location of seafloor hydrothermal field or not needs further verification. Hence, this paper provides a possible rule (the variation of analogy viscosity estimated by major element components in the basalts) for exploration the location of hydrothermal vents rather than a fully developed method.